Design and evaluation of finite and small antennas at 0.97 GHz for lightning remote sensing - Seah B.Y.; Ahmad M.R.; AlKahtani A.A.; Esa M.R.M.; Sidik M.A.B.; Baharin S.A.S.; Sabri M.H.M.; Yusop N.; Aziz M.Z.A.A.; Al-Khaleefa A.S.; Shairi N.A.; Kadir M.Z.A.A.B. (Mattingley Publishing, 2023)
Lightning; Microwave antennas; Natural frequencies; Omnidirectional antennas; Remote sensing; Signal to noise ratio; UHF devices; Computer simulation technology (CST); Design and evaluations; Finite; Narrow bipolar events; Omnidirectional radiation pattern; Small antenna; UHF sensor; UHF signal; Directional patterns (antenna)